2013
DOI: 10.15835/nsb529041
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Putrescine Application on Storability, Postharvest Quality and Antioxidant Activity of Two Iranian Apricot (Prunus armeniaca L.) Cultivars

Abstract: The limited postharvest storage life of apricot is the focus of this study. Presenting a solution to improve the postharvest storage of studied apricot cultivars is the goal. Studding the effect of different concentration of postharvest putrescine on quality attributes and antioxidant activity of two apricot cultivars during storage is the approach taken. The two apricot cultivars ('Lasgerdi' and 'Shahrodi') were harvested at the commercial ripening stage, and fruits were immerged in 1, 2, 3 and 4 mM putresc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 24 publications
13
22
0
Order By: Relevance
“…Additionally, foliar application of moringa leaf aqueous extract increased anthocyanidin content (Table 3) which considered natural antioxidants [38]. Moreover, increase ascorbic acid (Table 3) which closely correlated with antioxidant activity [39]. These results are in line with Nasira et al [18] who reported that aqueous extract of moringa increased the antioxidants of 'Kinnow' mandarin.…”
Section: Concentration Of Moringasupporting
confidence: 78%
“…Additionally, foliar application of moringa leaf aqueous extract increased anthocyanidin content (Table 3) which considered natural antioxidants [38]. Moreover, increase ascorbic acid (Table 3) which closely correlated with antioxidant activity [39]. These results are in line with Nasira et al [18] who reported that aqueous extract of moringa increased the antioxidants of 'Kinnow' mandarin.…”
Section: Concentration Of Moringasupporting
confidence: 78%
“…The relatively higher content of phenolic in ultrasound treated alone and combined with Put was observed. Similarly, previous studies showed that Put treatments had significant positive effect on phenolic compound of fruits (Shiri et al, 2012;Davarynejad et al, 2013). At the end of the storage, the highest total phenolic content was found in Put 2+ultrasound treatment (340.9 mg*100 g .…”
Section: Total Phenolic Contentsupporting
confidence: 74%
“…Postharvest application of Put, by immersion or vacuum infiltration, has been reported to delay fruit ripening and extend shelf life in some climacteric or nonclimacteric fruits such as lemon (Valero et al, 1998), apricot (Martinez-Romero et al, 2001), mango (Malik and Singh, 2005), strawberry (Khosroshahi et al, 2007), sweet cherry (Bal, 2012), plum (Serrano et al, 2003;Davarynejad et al, 2013) and peach (Bal, 2013). Champa et al (2014) reported that prestorage dip treatment of 0.5 mM Put or 0.5 mM Spd or 1.0 mM Spm for 5 min maintained the quality and extended the shelf life of grape cv.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of putrescine treatment to maintain ascorbic acid content may be ascribed to decreased or delayed ascorbate oxidase activity (Ishaq, Rathore, Majeed, Awan, & Zulfiqar‐Ali‐Shah, ). Similarly, prestorage application of putrescine retained ascorbic acid in apricot (Davarynejad, Zarei, Ardakani, & Nasrabadi, ).…”
Section: Resultsmentioning
confidence: 94%